2005
DOI: 10.1037/1524-9220.6.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Being a Man About It: Manhood Meaning Among African American Men.

Abstract: The present study is a qualitative examination of manhood meaning among African American men. Both the narrative process and definitions assigned were examined among 152 African American men residing in 5 metropolitan areas. Participants provided written responses to an open-ended question about the meaning of manhood. A content analysis was conducted using an open coding method (A. Strauss & J. Corbin, 1990), which revealed 15 distinct categories of meaning. Responsibilityaccountability emerged as the most fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
268
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(288 citation statements)
references
References 38 publications
18
268
1
Order By: Relevance
“…39 Some argue that since African-American men hold relatively lower social positions, they may delay healthcare utilization to symbolically exercise masculine dominion over their bodies. 27,40,41 Others posit that barriers to traditional male role fulfillment encourage African-American men to reject traditional masculinity, and adopt patterns of healthcare use that contradict dominant male behavioral norms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Some argue that since African-American men hold relatively lower social positions, they may delay healthcare utilization to symbolically exercise masculine dominion over their bodies. 27,40,41 Others posit that barriers to traditional male role fulfillment encourage African-American men to reject traditional masculinity, and adopt patterns of healthcare use that contradict dominant male behavioral norms.…”
Section: Introductionmentioning
confidence: 99%
“…We assessed the salience of traditional masculinity norms (e.g., having power and courage) to men's overall identity with a 9-item scale constructed from previous qualitative work on masculinity meaning among African-American men. 39 This measure assesses men's commitment to traditional masculinity norms and their likelihood of invoking them when making behavioral choices. 47,65 A mean score was computed from responses ranging from 1 ("not at all important") to 5 ("extremely important") (Cronbach's α = 0.79).…”
mentioning
confidence: 99%
“…Interventions that incorporate discussions of masculinity should expand and reframe the meaning of "manhood" beyond hypermasculine terms that may promote high-risk sexual practices. For example, Hammond and Mattis (2005) found that some African American men have developed more flexible definitions of masculinity, moving from a framework of African American manhood being seen as problematic "posturing" or defense mechanisms against historical racism and lack of economic opportunities to a construction of masculinity as a developmental and relational process promoting responsibilityaccountability to self, family, and community. In addition, though Oparanozie et al (2012) found that hypermasculine ideals contributed to concurrent sexual partnerships among African American men, strong African American racial identity contributed to a reduction in number of sexual partners, indicating that exploring how to focus on both masculinity and racial identity in efforts to reduce numbers of sexual partners may be a promising area of HIV prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, men who endorsed these cultural messages were less likely to refer male friends or acquaintances to mental health professionals (Vogel et al, 2013). Conceptually, how African American men define and embody their masculine identity may differ from White men (Hammond & Mattis, 2005). Bush and Bush (2013) explored three primary factors that have significantly influenced African American masculine identity including slavery, the matriarchal system commonly seen in African American communities, and the Civil Rights movement.…”
Section: African American Menmentioning
confidence: 99%